High-performance degradable epoxy infusion resin for wind turbine blades and preparation method and use thereof
Patent Information
- Application Number
- CN202611166073.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有体系仍存在不足:动态共价键的引入往往影响材料的力学性能和长期耐热性,且多数可降解环氧灌注树脂粘度较高,无法满足风电叶片真空灌注工艺的低粘度要求,难以直接应用于大型复合材料的整体成型
[0066]本发明针对现有可降解环氧灌注树脂粘度高、不适于灌注成型的问题,通过芳香醛-多元醇缩醛结构的设计与活性稀释剂、固化剂体系的协同优化,获得兼具低工艺粘度、长操作期和优异力学性能的可降解环氧灌注树脂。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of wind turbine blade composite material manufacturing technology, specifically to a high-performance biodegradable epoxy infusion resin for wind turbine blades, its preparation method, and its applications. Background Technology
[0002] Epoxy infusion resins are widely used in wind turbine blade manufacturing, aerospace composite materials, and automotive structural adhesives due to their excellent mechanical properties, adhesive properties, and chemical stability. The main body of wind turbine blades is typically made of glass fiber or carbon fiber reinforced epoxy infusion resin composites, where both the epoxy infusion resin matrix and the structural adhesive are typical thermosetting materials. However, traditional epoxy infusion resins, after curing, form a highly cross-linked three-dimensional network structure, exhibiting insoluble and infusible characteristics, making them difficult to recycle and reuse. With the continuous growth of global wind power installed capacity, a large number of blades are approaching their 20-25 year design lifespan, and the disposal of retired blades has become a key bottleneck restricting the green and sustainable development of the wind power industry. Existing methods such as mechanical recycling and heat recovery have limitations, including fiber performance degradation and the inability to utilize resins at high value.
[0003] In recent years, dynamic covalent bonds have gradually become an important research direction in the recyclability of thermosetting resins due to their ability to undergo network reconstruction or selective breakage under specific external stimuli. Among them, acetal bonds, with their characteristics of acid-responsive cleavage and stability under normal service conditions, are considered a class of dynamic covalent structures with potential for industrial applications. By introducing dynamic covalent bonds such as acetal bonds into epoxy infusion resins, the controlled degradation of materials under acidic and mild conditions can be achieved.
[0004] For example, existing studies have synthesized biodegradable epoxy infusion resins containing spirocyclic acetal structures using pentaerythritol and aromatic aldehydes as raw materials. However, existing systems still have shortcomings: the introduction of dynamic covalent bonds often affects the mechanical properties and long-term heat resistance of the materials, and most biodegradable epoxy infusion resins have high viscosity, which cannot meet the low viscosity requirements of the vacuum infusion process for wind turbine blades, making it difficult to directly apply them to the integral molding of large composite materials. Therefore, developing an epoxy infusion resin system that combines excellent mechanical properties, low process viscosity, and controllable degradation capability is of great significance for realizing the green recycling of wind power composite materials. Summary of the Invention
[0005] In order to overcome the above-mentioned defects of the prior art, the purpose of this invention is to provide a high-performance biodegradable epoxy infusion resin for wind turbine blades, its preparation method and its uses.
[0006] A high-performance biodegradable epoxy infusion resin for wind turbine blades, comprising, by weight percentage:
[0007] 60-85% biodegradable epoxy resin;
[0008] Epoxy resin 5-20%;
[0009] 5-15% reactive diluent;
[0010] High-efficiency diluent 1-10%;
[0011] Coupling agent 0.1-1%;
[0012] Defoamer 0.1-1%.
[0013] Component B, by mass percentage, comprises the following components:
[0014] Alicyclic amine curing agents 55-65%;
[0015] Polyetheramine curing agent 30-40%;
[0016] Accelerator 1-3%;
[0017] The biodegradable epoxy resin is shown in Formula 1:
[0018] ;
[0019] Wherein, Ar is shown in Equation 2, Equation 3 or Equation 4:
[0020]
[0021] Formula 2;
[0022]
[0023] Formula 3;
[0024]
[0025] Equation 4;
[0026] The R is shown in Equation 5, Equation 6 or Equation 7 as follows:
[0027]
[0028] Formula 5;
[0029]
[0030] Formula 6;
[0031]
[0032] Formula 7.
[0033] In a preferred embodiment of the present invention, the biodegradable epoxy resin is prepared by the following method:
[0034] (1) Aromatic aldehydes and polyols are subjected to acetalization in a reaction solvent under the action of an acid catalyst to obtain intermediate compounds containing cyclic acetal structures.
[0035] (2) The intermediate compound obtained in step (1) is mixed with epichlorohydrin and then subjected to a closed-ring epoxidation reaction. The biodegradable epoxy infusion resin is obtained by separation and purification.
[0036] The aromatic aldehyde compound is an aromatic compound with at least one phenolic hydroxyl group and one aldehyde group;
[0037] The polyol compound is any one or more of pentaerythritol, trimethylolpropane, or dipentaerythritol;
[0038] The molar ratio of the aldehyde group to the hydroxyl group in the aromatic aldehyde compound is 1:1.6-2.4.
[0039] The amount of epichlorohydrin used is 5-20 times, preferably 8-15 times, the molar amount of the intermediate compound.
[0040] The aromatic compound having at least one phenolic hydroxyl group and one aldehyde group is preferably one or more of vanillin, eugenol, and p-hydroxybenzaldehyde.
[0041] In a preferred embodiment of the present invention, the acid catalyst is any one or more of p-toluenesulfonic acid, sulfuric acid, or a solid acid, and is used in an amount of 0.5-5% of the molar amount of the aromatic aldehyde compound. P-Toluenesulfonic acid is preferred.
[0042] In a preferred embodiment of the present invention, the reaction solvent in step 1 is any one or more of N,N-dimethylformamide, toluene, cyclohexane, petroleum ether, or dichloromethane; the reaction temperature of the acetalization reaction is 60-120 °C; and the reaction time of the acetalization reaction is 2-8 hours.
[0043] In a preferred embodiment of the present invention, the closed-ring epoxidation reaction in step 2 specifically comprises:
[0044] First, an epoxidation reaction is catalyzed by a phase transfer catalyst. The reaction temperature of the epoxidation reaction is 60-90 °C, and the reaction time is 4-8 hours.
[0045] Then an alkaline solution is added, and the reaction continues at 60-80 °C for 2-4 hours to cause the chlorohydrin ether structure to undergo a ring-closing reaction to generate epoxy groups;
[0046] After the reaction was completed, excess epichlorohydrin was removed by vacuum distillation, by-product inorganic salts were removed by filtration, and the resin was then washed with water and dehydrated to obtain a biodegradable epoxy infusion resin containing an aromatic aldehyde-polyol acetal structure.
[0047] The phase transfer catalyst is any one or more of tetrabutylammonium bromide, tetrabutylammonium chloride, benzyltriethylammonium chloride, or tetrabutylammonium hydroxide.
[0048] The amount of the phase transfer catalyst is 1-5% of the molar amount of the intermediate compound.
[0049] The alkaline solution is an aqueous solution of sodium hydroxide.
[0050] In a preferred embodiment of the present invention, the epoxy resin is one or more of E54, E51 or bisphenol F type epoxy resin.
[0051] In a preferred embodiment of the present invention, the active diluent is any one or more of 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, or benzyl glycidyl ether;
[0052] The highly efficient diluent is any one or more of aliphatic monofunctional glycidyl ether, branched aliphatic glycidyl ether, and modified alicyclic glycidyl ether.
[0053] The coupling agent is γ-glycidoxypropyltrimethoxysilane;
[0054] The defoamer is a polyether-modified polysiloxane defoamer. A polyether-modified polysiloxane defoamer is preferred.
[0055] In a preferred embodiment of the present invention, the alicyclic amine curing agent is any one or more of IPDA, HMDA, HTDA or DMDC;
[0056] The polyetheramine curing agent is polyoxypropylene diamine with a molecular weight between 220 and 240;
[0057] The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0058] A method for preparing a high-performance biodegradable epoxy infusion resin for wind turbine blades, comprising:
[0059] Component A and component B are mixed evenly at a stoichiometric ratio of epoxy group to active amine hydrogen of 1:0.8-1.2. After vacuum degassing, the mixture is poured into a mold and cured at 30-60 ℃ for 2-6 hours, and then cured at 70-100 ℃ for 3-6 hours to obtain the high-performance biodegradable epoxy infusion resin for wind turbine blades.
[0060] The use of a high-performance biodegradable epoxy infusion resin for wind turbine blades, wherein the use is for preparing fiber-reinforced composite materials for vacuum infusion of wind turbine blades.
[0061] The use of a high-performance biodegradable epoxy resin for wind turbine blades is described, wherein the high-performance biodegradable epoxy resin for wind turbine blades is crushed to obtain blocky material.
[0062] The block was immersed in an acidic degradation solution and degraded at 40-100 °C for 0.5-10 hours.
[0063] The acidic degradation solution contains an acidic component, a polar organic solvent, and water. The acidic component is any one or more of hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, lactic acid, or citric acid. The polar organic solvent is any one or more of ethanol, ethylene glycol, propylene glycol, or acetone.
[0064] The H+ concentration of the acidic degradation solution is 0.1-3 mol / L.
[0065] The beneficial effects of this invention are as follows:
[0066] This invention addresses the problem that existing biodegradable epoxy injection resins have high viscosity and are unsuitable for injection molding. By designing an aromatic aldehyde-polyol acetal structure and synergistically optimizing the reactive diluent and curing agent system, a biodegradable epoxy injection resin with low process viscosity, long operating time, and excellent mechanical properties is obtained. Detailed Implementation
[0067] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below through embodiments. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, in the following descriptions, well-known structures and technologies are omitted to avoid unnecessarily obscuring the concept of the invention.
[0068] The biodegradable epoxy infusion resin of the present invention is achieved by introducing an acetal structure through an aromatic aldehyde-polyol system, as shown in Formula 1.
[0069] (1) Aromatic aldehydes and polyols are subjected to acetalization reaction under the action of acid catalyst to obtain intermediate compounds containing cyclic acetal structures.
[0070] Aromatic aldehydes have the structure Ar-CHO, where Ar represents an aromatic aldehyde residue. Aromatic aldehydes are aromatic compounds consisting of at least one phenolic hydroxyl group and one aldehyde group.
[0071] Polyol compounds have the structure R-(OH)n, where n≥2 and R is a polyol residue. Examples of polyol compounds include pentaerythritol, trimethylolpropane, or dipentaerythritol.
[0072] In aromatic aldehyde compounds, the molar ratio of the aldehyde group to the hydroxyl group in polyol compounds is 1:1.6-2.4. In the examples, a ratio of 1:2 is preferred.
[0073] (2) The intermediate compound obtained in step (1) is subjected to a closed-ring epoxidation reaction with epichlorohydrin in the presence of an alkali, and the biodegradable epoxy infusion resin is obtained by separation and purification.
[0074] Compared with the prior art, the preparation method of the present invention has mild reaction conditions and short time consumption, and produces a biodegradable epoxy resin containing an acetal structure.
[0075] Biodegradable epoxy infusion resins have rigid spirocyclic or bicyclic acetal structures. The rigidity of the cyclic structure is beneficial to improving the mechanical properties and heat resistance of epoxy infusion resins.
[0076] In this invention, epoxy resin is used to adjust the crosslinking network density, improve the toughness, interfacial bonding performance and long-term service stability of the cured product, while maintaining the acid-responsive decrosslinking ability provided by the acetal structure.
[0077] Reactive diluents are used to adjust the viscosity of the system and improve its processability.
[0078] The high-efficiency diluent has a significant viscosity-reducing effect and good glass fiber wettability, giving the biodegradable epoxy injection resin good injection efficiency.
[0079] The coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane (KH-560), which is used to improve the interfacial bonding performance between the resin matrix and the reinforcing fibers.
[0080] The defoamer is a polyether-modified polysiloxane defoamer, used to reduce the generation of bubbles during the curing process.
[0081] The polyetheramine curing agent is polyoxypropylene diamine with a molecular weight of approximately 230.
[0082] This invention constructs a crosslinked network that combines high performance with acid-responsive decrosslinking capability by introducing an acetal structure formed from aromatic aldehydes and polyols into the epoxy resin molecular structure. The rigid aromatic rings in the aromatic aldehydes can improve the rigidity of the resin chain segments and restrict molecular chain movement, which is beneficial to improving the glass transition temperature and mechanical properties of the cured material. The cyclic acetal structure has good stability in a neutral environment and can undergo selective cleavage under acidic conditions, thereby endowing the material with controllable chemical degradation properties.
[0083] Meanwhile, this invention employs a synergistic blend of biodegradable epoxy resin and traditional bisphenol-type epoxy resin, achieving acid-responsive crosslinking while maintaining high crosslinking density and long-term service stability. Furthermore, the introduction of reactive and high-efficiency diluents effectively reduces the system viscosity and improves the resin's wetting ability for reinforcing fibers, resulting in an epoxy infusion resin with excellent processing performance, mechanical properties, and chemical recyclability, meeting the application requirements of vacuum infusion molding processes for wind turbine blades.
[0084] The following is an illustration through specific embodiments:
[0085] I. Preparation of biodegradable epoxy resin monomers
[0086] Example 1 of synthesis of biodegradable epoxy resin monomers:
[0087] Preparation of vanillin-pentaerythritol-based biodegradable epoxy infusion resin (V-PER-EP)
[0088] In the first step, 152.15 g (1.0 mol) of vanillin and 68.08 g (0.5 mol) of pentaerythritol were weighed and added to a reactor equipped with a stirrer, thermometer, and water separator. 500 mL of N,N-dimethylformamide (DMF) and 200 mL of petroleum ether were added as reaction media, and 3.80 g (0.02 mol) of p-toluenesulfonic acid was added as a catalyst for the acetal reaction. The molar ratio of vanillin aldehyde group to pentaerythritol hydroxyl group was 1:2.
[0089] The reaction was heated under reflux at 110 °C for 6 hours, with water continuously removed using a water separator. After the reaction was complete, the mixture was cooled to room temperature, and the solvent was removed by vacuum distillation to obtain a vanillin-pentaerythritol acetal intermediate, which was a pale yellow solid.
[0090] In the second step, the above acetal intermediate (about 180 g) was added to 1200 g (about 13.0 mol) of epichlorohydrin, and 6.45 g (0.02 mol) of tetrabutylammonium bromide was added as a phase transfer catalyst.
[0091] The reaction was carried out at 70 °C for 6 hours to allow the hydroxyl groups in the intermediate to undergo an etherification reaction with epichlorohydrin.
[0092] Subsequently, 200 g of 40 wt% sodium hydroxide aqueous solution (2.0 mol NaOH) was slowly added, and the reaction was continued at 70 °C for 3 hours to allow the chlorohydrin ether structure to undergo a ring-closing reaction to generate epoxy groups.
[0093] After the reaction was completed, excess epichlorohydrin was recovered by vacuum distillation, and sodium chloride by-product was removed by filtration. The organic phase was washed with deionized water until neutral and dried with anhydrous sodium sulfate to obtain vanillin-pentaerythritol-based biodegradable epoxy infusion resin monomer (V-PER-EP), which is a pale yellow viscous liquid with an epoxy value of 0.42-0.48 mol / 100g, determined according to GB / T 1677 or ASTM D1652.
[0094] Example 2 of synthesis of biodegradable epoxy resin monomers:
[0095] Preparation of eugenol-trimethylolpropane degradable epoxy infusion resin (S-TMP-EP)
[0096] 182.18 g (1.0 mol) of eugenaldehyde and 67.09 g (0.5 mol) of trimethylolpropane were weighed and added to a reactor. 500 mL of toluene and 200 mL of cyclohexane were added as the reaction medium, and 3.80 g (0.02 mol) of p-toluenesulfonic acid was added as a catalyst. The mixture was heated under reflux at 110 °C for 8 hours, and the generated water was removed using a water separator. After the reaction was complete, the solvent was removed by vacuum distillation to obtain the eugenaldehyde-trimethylolpropane acetal intermediate.
[0097] The above acetal intermediate (approximately 210 g) was added to 1400 g (approximately 15.1 mol) of epichlorohydrin, followed by 7.0 g (0.022 mol) of tetrabutylammonium bromide. The reaction was carried out at 75 °C for 7 hours, followed by the addition of 220 g (2.2 mol) of 40 wt% sodium hydroxide aqueous solution, and the reaction was continued for another 3 hours.
[0098] The post-treatment was the same as in Synthesis Example 1, yielding eugenol-trimethylolpropane degradable epoxy infusion resin monomer (S-TMP-EP), a pale yellow viscous liquid with an epoxy value of 0.40-0.46 mol / 100g, determined according to GB / T 1677 or ASTM D1652.
[0099] II. Resin Formulation and Process Validation
[0100] Example 1
[0101] This embodiment provides a method for preparing and degrading a biodegradable epoxy resin material. The method uses the vanillin-pentaerythritol-based biodegradable epoxy resin prepared in Synthesis Example 1, wherein the biodegradable epoxy resin accounts for 75%, the traditional epoxy infusion resin accounts for 14%, and other additives account for 11%.
[0102] Preparation of component A (per 100 parts):
[0103] Vanillin-pentaerythritol-based biodegradable epoxy infusion resin monomer (V-PER-EP) of Synthetic Example 1: 75 parts;
[0104] Epoxy resin E-51: 14 parts;
[0105] 1,4-Butanediol diglycidyl ether: 8 parts;
[0106] n-Butyl glycidyl ether: 2 parts;
[0107] γ-glycidyl etheroxypropyltrimethoxysilane (KH-560): 0.5 parts;
[0108] Polyether-modified polysiloxane defoamer: 0.5 parts;
[0109] Weigh the above components according to the specified ratio, stir and mix them evenly, and then degas them under vacuum to obtain component A.
[0110] Preparation of component B (per 100 parts):
[0111] IPDA: 60 copies
[0112] Polyetheramine D230: 38 parts
[0113] DMP-30 accelerator: 2 parts
[0114] After weighing the above components according to the specified ratio, stir and mix them evenly at room temperature to obtain component B.
[0115] Preparation of biodegradable epoxy resin material in Example 1:
[0116] After mixing components A and B according to the formula, they are separately degassed under vacuum. They are then mixed at a stoichiometric ratio of 1:1 between epoxy groups and active amine hydrogens, stirred evenly, and degassed under vacuum before being poured into a metal mold coated with a release agent.
[0117] The initial viscosity of the mixed resin at 25°C is 200 mPa·s, and the working time is 3.0 h.
[0118] A segmented curing process was adopted: curing at 30-50 ℃ for 4 hours, and curing at 70-90 ℃ for 5 hours. After curing, the product was allowed to cool naturally to room temperature and then demolded to obtain the biodegradable epoxy resin cured product of Example 1.
[0119] Degradation performance test of biodegradable epoxy resin material in Example 1:
[0120] The biodegradable epoxy resin cured product from Example 1 was broken into small pieces of approximately 5 mm × 5 mm × 5 mm. 2.0 g of each piece was weighed and immersed in 50 mL of acidic degradation solution (1.0 mol / L HCl / acetone / water = 9:1:1, volume ratio), and heated and stirred at 80 °C. Samples were taken periodically to observe the degradation process.
[0121] Example 2
[0122] This embodiment provides a method for preparing and degrading a biodegradable epoxy resin material. The biodegradable epoxy resin of Synthesis Example 2 is used, with the biodegradable epoxy resin accounting for 75%, the traditional epoxy infusion resin accounting for 14%, and other additives accounting for 11%.
[0123] Preparation of component A (per 100 parts):
[0124] Synthesized Example 2: Syringaldehyde-trimethylolpropane degradable epoxy resin (S-TMP-EP): 75 parts;
[0125] E-51: 14 copies;
[0126] 1,4-Butanediol diglycidyl ether: 8 parts;
[0127] n-Butyl glycidyl ether: 2 parts;
[0128] KH-560 coupling agent: 0.5 parts;
[0129] Polyether-modified polysiloxane defoamer: 0.5 parts;
[0130] Preparation of component B (per 100 parts):
[0131] IPDA: 60 copies;
[0132] Polyetheramine D230: 38 parts;
[0133] DMP-30 accelerator: 2 parts;
[0134] Preparation of biodegradable epoxy resin materials:
[0135] The preparation method is the same as in Example 1. The initial viscosity of the mixed resin at 25 °C is 180 mPa·s, and the working time is 3.0 h.
[0136] Example 3
[0137] This embodiment provides a method for preparing and degrading a biodegradable epoxy resin material. The vanillin-pentaerythritol-based biodegradable epoxy resin of Synthesis Example 1 is used. The biodegradable epoxy resin accounts for 60%, the traditional epoxy resin accounts for 29%, and other additives account for 11%.
[0138] Preparation of component A (per 100 parts):
[0139] Vanillin-pentaerythritol-based biodegradable epoxy resin (V-PER-EP) of Synthetic Example 1: 60 parts;
[0140] E-51: 29 copies;
[0141] 1,4-Butanediol diglycidyl ether: 8 parts;
[0142] n-Butyl glycidyl ether: 2 parts;
[0143] KH-560 coupling agent: 0.5 parts;
[0144] Polyether-modified polysiloxane defoamer: 0.5 parts;
[0145] Preparation of component B (per 100 parts):
[0146] IPDA: 60 copies;
[0147] Polyetheramine D230: 38 parts;
[0148] DMP-30 accelerator: 2 parts;
[0149] Preparation of biodegradable epoxy resin materials:
[0150] The preparation method is the same as in Example 1. The initial viscosity of the mixed resin at 25 °C is 160 mPa·s, and the working time is 3.5 h.
[0151] Example 4
[0152] This embodiment provides a method for preparing and degrading a biodegradable epoxy resin material. The vanillin-pentaerythritol-based biodegradable epoxy resin of Synthesis Example 1 is used. The biodegradable epoxy resin accounts for 70%, the traditional epoxy resin accounts for 19%, and other additives account for 11%.
[0153] Preparation of component A (per 100 parts):
[0154] Vanillin-pentaerythritol-based biodegradable epoxy resin (V-PER-EP) of Synthetic Example 1: 70 parts;
[0155] E-51: 19 copies;
[0156] 1,4-Butanediol diglycidyl ether: 8 parts;
[0157] n-Butyl glycidyl ether: 2 parts;
[0158] KH-560 coupling agent: 0.5 parts;
[0159] Polyether-modified polysiloxane defoamer: 0.5 parts;
[0160] Preparation of component B (per 100 parts):
[0161] IPDA: 60 copies;
[0162] Polyetheramine D230: 38 parts;
[0163] DMP-30 accelerator: 2 parts;
[0164] Preparation of biodegradable epoxy resin materials:
[0165] The preparation method is the same as in Example 1. The initial viscosity of the mixed resin at 25 °C is 200 mPa·s, and the working time is 3.0 h.
[0166] Example 5
[0167] This embodiment provides a method for preparing and degrading a biodegradable epoxy resin material. The vanillin-pentaerythritol-based biodegradable epoxy resin of Synthesis Example 1 is used. The biodegradable epoxy resin accounts for 80%, the traditional epoxy resin accounts for 9%, and other additives account for 11%.
[0168] Preparation of component A (per 100 parts):
[0169] Vanillin-pentaerythritol-based biodegradable epoxy resin (V-PER-EP) of Synthetic Example 1: 80 parts;
[0170] E-51: 9 copies;
[0171] 1,4-Butanediol diglycidyl ether: 8 parts;
[0172] n-Butyl glycidyl ether: 2 parts;
[0173] KH-560 coupling agent: 0.5 parts;
[0174] Polyether-modified polysiloxane defoamer: 0.5 parts;
[0175] Preparation of component B (per 100 parts):
[0176] IPDA: 60 copies;
[0177] Polyetheramine D230: 38 parts;
[0178] DMP-30 accelerator: 2 parts;
[0179] Preparation of biodegradable epoxy resin materials:
[0180] The preparation method is the same as in Example 1. The initial viscosity of the mixed resin at 25 °C is 220 mPa·s, and the working time is 2.5 h.
[0181] Comparative Example 1 (Pure Traditional Epoxy Resin E-51)
[0182] Component A (per 100 parts):
[0183] E-51 90 copies;
[0184] 9 parts of 1,4-butanediol diglycidyl ether;
[0185] KH-560 0.5 copies;
[0186] 0.5 parts of defoamer.
[0187] Component B (per 100 parts):
[0188] IPDA 60 copies;
[0189] 38 parts of polyetheramine D230;
[0190] Two copies of DMP-30.
[0191] The preparation method is the same as in Example 1. The initial viscosity of the mixed resin at 25 °C is 280 mPa·s, and the working time is 3.0 h.
[0192] The epoxy infusion resin cured products prepared in the embodiments and comparative examples of this application were tested, and the results of the epoxy infusion resin cured products are shown in Table 1.
[0193] Table 1. Performance Comparison of Epoxy Injection Resin Compositions in Various Examples and Comparative Examples
[0194]
[0195] As shown in Table 1, the aromatic aldehyde-polyol-based biodegradable epoxy infusion resin systems provided by this invention all exhibit excellent comprehensive performance. The resin systems obtained in each embodiment, while maintaining low initial viscosity and suitable operating time, all possess high glass transition temperature, mechanical properties, and dimensional stability after curing, meeting the basic requirements of wind turbine blade vacuum infusion processes for low viscosity, high wettability, long pot life, and high-performance cured materials.
[0196] Examples 1-5 demonstrate that the present invention uses a biodegradable epoxy resin containing an aromatic aldehyde-polyol acetal structure as the main resin, and synergistically blends it with a traditional epoxy casting resin. This ensures good casting processing performance while maintaining good thermal and mechanical properties of the cured material. Different aromatic aldehyde and polyol structures can successfully construct biodegradable epoxy resin systems, indicating that the present invention has good structural universality. Furthermore, the biodegradable epoxy resin exhibits good compatibility with traditional epoxy resins within a certain ratio range, forming a cured network that meets the application requirements of wind turbine blades.
[0197] Compared with traditional epoxy infusion resins, the most significant feature of the resin system compounded in this invention is that, while maintaining compatibility with existing wind turbine blade infusion processes, an acid-responsive acetal structure is introduced. This allows the cured resin network to remain stable during service, while under specific acidic conditions, it can undergo chemical decrosslinking, achieving controlled degradation of the resin matrix and effective separation of reinforcing fibers. This provides a new solution for the resource recycling of composite materials for decommissioned wind turbine blades.
[0198] In summary, this invention proposes to use an aromatic aldehyde-polyol acetal structure as a dynamic pyrolytic structural unit, and to construct a high cross-linking density network by synergistically combining traditional bisphenol epoxy resin and dynamic epoxy resin. This achieves a synergistic unity among low viscosity infusion, high performance service, and mild chemical recycling, while maintaining compatibility with existing vacuum infusion processes for wind turbine blades, and realizing the high-value recycling of thermosetting epoxy composite materials.
[0199] The foregoing has shown and described the basic principles and main features of the invention and the advantages of the invention.
[0200] Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope. All such changes and modifications fall within the scope of the present invention as claimed, which is defined by the appended claims and their equivalents.
Claims
1. A high-performance biodegradable epoxy infusion resin for wind turbine blades, characterized in that, Calculated as a percentage by mass, including: 60-85% biodegradable epoxy resin; Epoxy resin 5-20%; 5-15% reactive diluent; High-efficiency diluent 1-10%; Coupling agent 0.1-1%; Defoamer 0.1-1%. Component B, by mass percentage, comprises the following components: Alicyclic amine curing agents 55-65%; Polyetheramine curing agent 30-40%; Accelerator 1-3%; The biodegradable epoxy resin is shown in Formula 1: ; Wherein, Ar is shown in Equation 2, Equation 3 or Equation 4: Formula 2; Formula 3; Equation 4; The R is shown in Equation 5, Equation 6 or Equation 7 as follows: Formula 5; Formula 6; Formula 7.
2. The high-performance biodegradable epoxy infusion resin for wind turbine blades as described in claim 1, characterized in that, The biodegradable epoxy resin is prepared by the following method: (1) Aromatic aldehydes and polyols are subjected to acetalization in a reaction solvent under the action of an acid catalyst to obtain intermediate compounds containing cyclic acetal structures. (2) The intermediate compound obtained in step (1) is mixed with epichlorohydrin and then subjected to a closed-ring epoxidation reaction. The biodegradable epoxy infusion resin is obtained by separation and purification. The aromatic aldehyde compound is an aromatic compound with at least one phenolic hydroxyl group and one aldehyde group; The polyol compound is any one or more of pentaerythritol, trimethylolpropane, or dipentaerythritol; The molar ratio of the aldehyde group to the hydroxyl group in the aromatic aldehyde compound is 1:1.6-2.
4. The amount of epichlorohydrin used is 5-20 times the molar amount of the intermediate compound.
3. The high-performance biodegradable epoxy infusion resin for wind turbine blades as described in claim 2, characterized in that, The aromatic compound having at least one phenolic hydroxyl group and one aldehyde group is any one or more of vanillin, eugenol, and p-hydroxybenzaldehyde; The acid catalyst is any one or more of p-toluenesulfonic acid, sulfuric acid, or solid acid, and its amount is 0.5-5% of the molar amount of the aromatic aldehyde compound. The reaction solvent in step 1 is any one or more of N,N-dimethylformamide, toluene, cyclohexane, petroleum ether, or dichloromethane; the reaction temperature of the acetalization reaction is 60-120 °C; and the reaction time of the acetalization reaction is 2-8 hours.
4. The high-performance biodegradable epoxy infusion resin for wind turbine blades as described in claim 2, characterized in that, The closed-ring epoxidation reaction in step 2 is specifically as follows: First, an epoxidation reaction is catalyzed by a phase transfer catalyst. The reaction temperature of the epoxidation reaction is 60-90 °C, and the reaction time is 4-8 hours. Then an alkaline solution is added, and the reaction continues at 60-80 °C for 2-4 hours to cause the chlorohydrin ether structure to undergo a ring-closing reaction to generate epoxy groups; After the reaction was completed, excess epichlorohydrin was removed by vacuum distillation, by-product inorganic salts were removed by filtration, and the resin was washed with water and dehydrated in sequence to obtain a biodegradable epoxy infusion resin containing an aromatic aldehyde-polyol acetal structure. The phase transfer catalyst is any one or more of tetrabutylammonium bromide, tetrabutylammonium chloride, benzyltriethylammonium chloride, or tetrabutylammonium hydroxide. The amount of the phase transfer catalyst is 1-5% of the molar amount of the intermediate compound; The alkaline solution is an aqueous solution of sodium hydroxide.
5. The high-performance biodegradable epoxy infusion resin for wind turbine blades as described in claim 1, characterized in that, The epoxy resin is one or more of E54, E51 or bisphenol F type epoxy resin; the reactive diluent is any one or more of 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether or benzyl glycidyl ether. The highly efficient diluent is any one or more of aliphatic monofunctional glycidyl ether, branched aliphatic glycidyl ether, and modified alicyclic glycidyl ether. The coupling agent is γ-glycidoxypropyltrimethoxysilane; The defoamer is a polyether-modified polysiloxane defoamer. A polyether-modified polysiloxane defoamer is preferred. The alicyclic amine curing agent is any one or more of IPDA, HMDA, HTDA, or DMDC; The polyetheramine curing agent is polyoxypropylene diamine with a molecular weight between 220 and 240; The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
6. A method for preparing a high-performance biodegradable epoxy infusion resin for wind turbine blades as described in any one of claims 1-5, characterized in that, include: Component A and component B are mixed evenly at a stoichiometric ratio of epoxy group to active amine hydrogen of 1:0.8-1.
2. After vacuum degassing, the mixture is poured into a mold and cured at 30-60 ℃ for 2-6 hours, and then cured at 70-100 ℃ for 3-6 hours to obtain the high-performance biodegradable epoxy infusion resin for wind turbine blades.
7. The use of a high-performance biodegradable epoxy infusion resin for wind turbine blades as described in any one of claims 1-5, characterized in that, The application is for preparing fiber-reinforced composite materials for vacuum infusion of wind turbine blades.
8. The use of a high-performance biodegradable epoxy infusion resin for wind turbine blades as described in any one of claims 1-5, characterized in that, The wind turbine blades can be degraded by crushing them with high-performance biodegradable epoxy resin to obtain block-shaped materials. The block was immersed in an acidic degradation solution and degraded at 40-100 °C for 0.5-10 hours. The acidic degradation solution contains an acidic component, a polar organic solvent, and water. The acidic component is any one or more of hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, lactic acid, or citric acid. The polar organic solvent is any one or more of ethanol, ethylene glycol, propylene glycol, or acetone. The H+ concentration of the acidic degradation solution is 0.1-3 mol / L.